Os estudos de Thomas Hunt Morgan sobre determinação de sexo (1900-1914): herança citoplasmática, cromossômica e outras possibilidades - Brito, Ana Paula Oliveira Pereira de Morais (2008)
The present research analyses Thomas Hunt Morgan s studies on sex-determination (1900-1913) and tries to elucidate: which were Morgan s main hypotheses to explain such a phenomenon; whether they were well grounded or not and whether there were any changes in his thought in that period. Besides that, it tries to find whether Morgan s contribution concerning sex-determination were significant as compared to those of other scientists of his time, as well as the kind of strategy he used to become the most frequently cited scientist on the subject. This thesis contains an introduction and five chapters. Chapter 1 deals with the hereditary precedents and the general scientific context in which Morgan presented his contributions concerning the subject. It also presents a short account of his career, background and professional interests. Chapter 2 describes the different explanations concerning sex-determination presented by several scientists in the first decade of the 20th century. Chapter 3 discusses some results obtained by Morgan in his studies on sex-determination during the period from 1900 to 1910. Chapter 4 discusses whether the evidence got from Morgan s studies on sex-determination from 1910-11 to 1913 was enough to explain his change of opinion concerning the relationship between sex-determination, chromosomes and Mendel´s principles. Chapter 5 tries to answer the questions presented in the Introduction and provides some final remarks on the subject. This study led to the conclusion that Morgan s belief in a cytoplasmic inheritance of sex-determination till 1910 was grounded on the evidence he got from his embryological studies, as well as his studies on sex-determination in parthenogenetic insects. Even when he admitted in 1909 that chromosomes could contribute in some way to this phenomenon, he supposed that this was a quantitative effect. The evidence got from Morgan s studies from 1910-1911 to 1913 related to sex-linked inheritance in Drosophila, in our view, were not enough to justify his change of mind on the subject by adopting a quantitative Mendelian-chromosome interpretation. Besides that, his old criticisms on the Mendelian chromosome theory as a whole were not answered. This study confirms the interpretation that Morgan s change of view was mainly due to a professional strategy, since he considered this could be a fruitful working hypothesis of work. He admitted students which were of a low academic status in spite of being skilful and well-trained in cytology. Moreover, he chose a cheap and easily breeding experimental material and wrote several works individually or together with his collaborators in a popular style, such as Heredity an sex. Morgan s strategies worked, since after 1910-1911 the works of the Drosophila group were widely cited in the relevant literature